2019
DOI: 10.1128/mbio.01663-19
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism-Mediated Disruption of EGR1/ADAM10 Pathway Confers the Risk of Sepsis Progression

Abstract: Increasing evidence has indicated that single nucleotide polymorphisms (SNPs) are related to the susceptibility of sepsis and might provide potential evidence for the mechanisms of sepsis. Our recent preliminary study showed that the ADAM10 genetic polymorphism was clinically associated with the development of sepsis, and little is known about the underlying mechanism. The aim of this study was to confirm the association between the ADAM10 promoter rs653765 G→A polymorphism and the progression of sepsis and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Additionally, we found that the inhibition of EGR1 can reduce the in ammatory response and improve the survival of LPS-induced endotoxemia mice, which was consistent with our previous study [48]. However, another study reported that Egr-1 de ciency via gene knock-out did not positively affect survival and plasma levels of TNF in endotoxemic mice [49].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found that the inhibition of EGR1 can reduce the in ammatory response and improve the survival of LPS-induced endotoxemia mice, which was consistent with our previous study [48]. However, another study reported that Egr-1 de ciency via gene knock-out did not positively affect survival and plasma levels of TNF in endotoxemic mice [49].…”
Section: Discussionsupporting
confidence: 92%
“…26 The ADAM10 rs514049-rs653765 CA promoter haplotype could functionally modulate ADAM10 promoter activity by altering the binding of the EGR1 (early growth response protein 1) transcription factor to the ADAM10 promoter, affecting the transcription of ADAM10. 26,37 One study containing 10 people with mild cognitive impairments (MCIs), 25 AD patients, and 10 healthy controls (HCs) in a Brazilian population, found that plasma ADAM10 levels were significantly higher in AD patients than in HCs, while the concentration of plasma ADAM10 in PD patients remains unknown. 38 variants have also been observed in AD, 8,15,26,38 However, the role of ADAM10 in the occurrence and development of PD is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Province. The patients were enrolled in the study if they met the following inclusion criteria: 1) the patients were older than 18 years of age and belonged to the Chinese Han population; 2) the diagnosis of sepsis, severe sepsis, or septic shock was established according to the International Sepsis De nitions Conference [30]; and 3) the patients had a probability of survival greater than 24 hours. Patients were excluded from this study if they had diabetes, malignant tumors, human immunode ciency virus, or autoimmune diseases or were pregnant, readmitted to a hospital or receiving immunosuppressive therapy, corticosteroid therapy or chemoradiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…EGR1 antisense oligonucleotide (As-ODN) (5'-TACCGTCGCCGGTTC-3') was constructed to inhibit EGR1 by targeting the corresponding DNA sequence. The EGR1 sense ODN (S-ODN) (5'-TCGTGCCGCTGCCAT-3') was used as a negative control [30,31]. All ODNs were synthesized by Takara Biomedical Technology Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%